Treatment process for improving three-point bending fatigue limit of thin-walled titanium alloy test piece
By introducing gradient structures and residual compressive stresses on the surface of thin-walled titanium alloy specimens using femtosecond laser shock peening technology, the problems of deformation and stress concentration caused by traditional mechanical strengthening are solved, thereby improving the fatigue performance and service reliability of thin-walled titanium alloy components.
Patent Information
- Application Number
- CN202511325883.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-17
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2045-09-17
AI Technical Summary
Existing technologies struggle to achieve uniform strengthening while maintaining the geometric accuracy of thin-walled titanium alloy components. Furthermore, mechanical rolling strengthening can easily lead to deformation and stress concentration, affecting service life and reliability.
Femtosecond laser shock peening technology is employed to introduce gradient structures and residual compressive stress by optimizing the combination of femtosecond laser energy and shock frequency, thereby suppressing fatigue crack initiation and preventing the expansion of the heat-affected zone and specimen deformation.
It significantly improves the bending fatigue performance of thin-walled titanium alloy specimens, ensures uniform stress distribution, and extends the service life and reliability of aerospace components.
Smart Images

Figure CN120831289B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of improving the fatigue resistance of metal materials, in particular to a processing technology for improving the three-point bending fatigue limit of a thin-walled titanium alloy test piece. BACKGROUND
[0002] Thin-walled TC4 titanium alloy is widely used in key load-bearing components in the aviation field, such as wing skin, transmission diaphragm, and engine blade leading edge, due to its excellent specific strength, corrosion resistance, and high-temperature performance. These components often bear high-frequency cyclic bending loads during service, and fatigue cracks are easily initiated and propagated in the stress concentration area, leading to structural failure. Especially for thin-walled components, their geometric characteristics make the material more sensitive to surface defects, and traditional fatigue strengthening methods are difficult to achieve uniform strengthening effect while ensuring the geometric precision of the components, which severely restricts the service life and reliability of the components. Currently, surface strengthening and mechanical rolling strengthening technologies (such as shot peening) for thin-walled titanium alloys can introduce residual compressive stress to delay the initiation of fatigue cracks, but there are the following limitations when strengthening thin-walled components: 1. Mechanical impact can easily cause macroscopic deformation of thin-walled components, affecting the assembly precision of the components; 2. Traditional mechanical strengthening techniques are difficult to achieve uniform distribution of residual stress field on complex thin-walled components, which can easily cause local stress concentration. SUMMARY
[0003] The present application aims to, for example, provide a processing technology for improving the three-point bending fatigue limit of a thin-walled titanium alloy test piece, which can optimize the combination of femtosecond laser energy and impact frequency to impact strengthen a thin-walled TC4 titanium alloy three-point bending test piece, introduce a gradient structure and residual compressive stress in the surface layer using high-strain-rate plastic deformation induced by ultrafast laser, inhibit the initiation of fatigue cracks, and avoid the expansion of the heat-affected zone and deformation of the test piece, thereby improving the bending fatigue performance.
[0004] Embodiments of the present application can be implemented as follows:
[0005] In a first aspect, the present application provides a processing technology for improving the three-point bending fatigue limit of a thin-walled titanium alloy test piece, comprising the following steps:
[0006] Step s100, pretreating a TC4 titanium alloy sheet to obtain a test piece;
[0007] Step s200, using ultrafast laser impact strengthening to treat the test piece;
[0008] Step s300, setting a load and performing three-point fatigue experiments on the test pieces before and after strengthening;
[0009] Step s400, calculating the bending fatigue limit of the test pieces before and after strengthening, and comparing the strengthening mechanisms.
[0010] In an optional embodiment, the step s100 comprises cutting a TC4 titanium alloy sheet according to a set size to obtain a cutting piece, grinding and polishing the cutting piece, and then ultrasonic cleaning the cutting piece to obtain the test piece after drying.
[0011] In an optional embodiment, the step s200 comprises positioning the test piece on a machining platform of a femtosecond laser, setting working parameters of the femtosecond laser, and scanning and strengthening the surface of the test piece by the femtosecond laser with the set working parameters.
[0012] In an optional embodiment, in the step s200, the surface of the test piece is scanned and strengthened by the femtosecond laser in a "Z" shaped scanning path.
[0013] In an optional embodiment, in the step s200, the working parameters are set as follows:
[0014] The pulse width of the femtosecond laser is set to 290-1000 fs, the pulse energy of the femtosecond laser is set to 50-200 μJ, the repetition frequency of the femtosecond laser is set to 45-55 KHz, the spot diameter of the femtosecond laser is set to 25-35 μm, and the overlap rate of the femtosecond laser is set to 45-55%.
[0015] In an optional embodiment, in the step s300, the test piece is ultrasonic cleaned by anhydrous ethanol, the cleaned test piece is positioned on a three-point bending clamp of a fatigue testing machine, and the fatigue testing machine is started after setting a loading load.
[0016] In an optional embodiment, before the test piece is positioned on the three-point bending clamp, the distance L between the lower two loading rollers of the three-point bending clamp is adjusted by the following formula:
[0017] L= (D+3a)±a / 2, wherein D is the diameter of the loading roller, and a is the thickness of the test piece, both in mm.
[0018] In an optional embodiment, in the step s400, the three-point bending fatigue test is performed by using a step-by-step loading method, and the loading parameters are set as follows: stress ratio R=0.1, loading frequency 100 Hz, maximum bending stress set to 30% of the material yield strength, each level cycle set to 1×106, if the test piece does not fail after the cycle under the load, the next level cycle is automatically entered according to the stress ratio R=0.1, and the cycle is repeated until the test piece fails, and each test group contains at least 5 parallel test pieces.
[0019] In an optional embodiment, in step s400, the bending fatigue limit σ of the specimen before and after strengthening is obtained using the following formula. HCF :
[0020] σ HCF =σ pr +N f (σ f -σ pr ) / 10^6, where σ pr The stress value is the first-order stress value before fracture failure of the fatigue specimen, N. f σ represents the number of cycles the specimen undergoes at the fracture stress level. f The maximum stress level was determined; experimental data were recorded, and the strengthening mechanism was analyzed based on the experimental data.
[0021] Secondly, the present invention provides a processing system applied to any of the foregoing embodiments for improving the three-point bending fatigue limit of thin-walled titanium alloy specimens, comprising:
[0022] The equipment includes a pretreatment device, a femtosecond laser, and a fatigue testing machine. The pretreatment device is used to obtain a specimen, and the femtosecond laser is used to emit a laser beam onto the surface of the specimen to strengthen it. The fatigue testing machine is used to perform three-point fatigue tests on the specimens before and after strengthening.
[0023] The beneficial effects of the embodiments of the present invention include, for example:
[0024] In summary, the processing technology provided in this embodiment, which strengthens specimens using ultrafast laser shock peening, utilizes femtosecond laser shock peening technology. This technology employs a high strain rate shock wave generated when an extremely short pulse (on the order of 10⁻¹⁵ seconds) interacts with the material, inducing plastic deformation and forming a gradient structure on the material surface. Simultaneously, it introduces high-amplitude residual compressive stress, offering advantages such as controllable energy input and a minimal heat-affected zone, making it particularly suitable for localized strengthening of thin-walled components. Furthermore, the ultrashort pulse characteristics of the femtosecond laser allow for precise control of energy input, avoiding thermal accumulation effects and macroscopic deformation of the specimen. Secondly, the controllable micron-sized spot size of the femtosecond laser induces high-amplitude compressive residual stress on the material surface, effectively suppressing the initiation and propagation of fatigue cracks while ensuring uniform stress distribution. This process offers high controllability and is suitable for complex curved thin-walled components or microscale regions, providing an efficient and reliable solution for the long-life design of aerospace thin-walled titanium alloy components (such as wing skins, thin-walled membrane disks, and engine blade leading edges), significantly improving their service reliability and lifespan. Attached Figure Description
[0025] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 This is a flowchart of the process for improving the three-point bending fatigue limit of thin-walled titanium alloy specimens in this embodiment;
[0027] Figure 2 This is a schematic diagram illustrating the application of the three-point bending fatigue testing machine in this embodiment;
[0028] Figure 3 This is a schematic diagram of the operation of the femtosecond laser in this embodiment;
[0029] Figure 4 This is a three-point bending fatigue limit diagram based on stress data parameter optimization in this embodiment.
[0030] icon:
[0031] 100 - Specimen; 200 - Support roller; 300 - Loading roller; 400 - Laser source; 410 - Beam expander; 420 - Reflector; 430 - Scanning galvanometer; 440 - Field lens; 450 - Spot analyzer; 460 - Controller. Detailed Implementation
[0032] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.
[0033] Therefore, the following detailed description of the embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.
[0034] It should be noted that similar labels and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.
[0035] In the description of this invention, it should be noted that if terms such as "upper," "lower," "inner," or "outer" are used to indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, or the orientation or positional relationship in which the product of this invention is usually placed, they are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this invention.
[0036] Furthermore, the terms "first" and "second" are used only to distinguish descriptions and should not be interpreted as indicating or implying relative importance.
[0037] It should be noted that, where there is no conflict, the features in the embodiments of the present invention can be combined with each other.
[0038] Please refer to Figure 1 This embodiment provides a process for improving the three-point bending fatigue limit of thin-walled titanium alloy specimens, including the following steps:
[0039] Step s100: Pre-treat TC4 titanium alloy sheet to obtain specimen 100;
[0040] Step s200: Specimen 100 is subjected to ultrafast laser shock peening treatment;
[0041] Step s300: Set the load and perform three-point fatigue tests on the specimen 100 before and after strengthening.
[0042] Step s400: Calculate the bending fatigue limit of specimen 100 before and after strengthening, and conduct a comparative analysis of the strengthening mechanism.
[0043] As described above, the process for improving the three-point bending fatigue limit of thin-walled titanium alloy specimens provided in this embodiment utilizes the ultrashort pulse characteristics of femtosecond lasers to precisely control energy input, avoiding thermal accumulation effects and macroscopic deformation of the specimen. Secondly, the femtosecond laser's controllable micron-level spot induces high-amplitude compressive residual stress on the material surface, effectively suppressing the initiation and propagation of fatigue cracks while ensuring uniform stress distribution. This process offers high controllability and is suitable for complex curved thin-walled components or microscale regions, providing an efficient and reliable solution for the long-life design of aerospace thin-walled titanium alloy components (such as wing skins, thin-walled film disks, and engine blade leading edges), significantly improving their service reliability and lifespan.
[0044] The following embodiments illustrate the details of the processing technology for improving the three-point bending fatigue limit of thin-walled titanium alloy specimens in this application by way of example.
[0045] In this embodiment, optionally, the processing technology includes step s100, pre-treating the TC4 titanium alloy sheet to obtain specimen 100. Specifically, according to the requirements of GB / T 38915-2020 "High-Temperature Titanium Alloy Forgings for Aerospace Applications" technical standard, the main mechanical properties of TC4 titanium alloy material include: tensile strength not less than 970 MPa, elastic modulus approximately 110 GPa, and Poisson's ratio 0.342. During the preparation of specimen 100, the forged TC4 titanium alloy is first processed into a regular 30 mm × 15 mm × 1 mm disc using an electrical discharge wire cutting process according to GB / T 232-2024 for the three-point bending test. Subsequently, the surface of the disc is treated by mechanical grinding and polishing, which can effectively reduce the surface roughness and obtain a smooth surface that meets the requirements of ultrafast laser surface strengthening treatment. Simultaneously, to further remove surface contaminants, specimen 100 can be placed in an ultrasonic cleaning device using high-purity anhydrous ethanol as the cleaning medium. Ultrasonic oscillation removes oil stains, oxide layers, and other deposits from the surface of the cutting disc. After drying, the surface of the cutting disc is ensured to meet the cleanliness requirements for ultrafast laser processing. The dried cutting disc is the specimen 100 to be processed. This pretreatment process significantly improves the interaction between the subsequent ultrafast laser pulse and the material surface, thereby enhancing the strengthening effect of specimen 100.
[0046] Step s200 involves strengthening the specimen 100 using an ultrafast laser shock peening treatment. Specifically, the pre-treated specimen 100 is fixed on a three-axis machining platform of a femtosecond laser. The main parameters of the femtosecond laser are as follows: pulse width 290-1000 fs, pulse energy 50-200 μJ, repetition rate 45-55 kHz, spot diameter 25-35 μm, and overlap ratio 45-55%. The operating principle of the femtosecond laser is as follows: the laser light source outputs laser light, which is then applied to the material surface by the femtosecond laser beam expander 410, reflector 420, scanning galvanometer 430, and field mirror 440. During actual operation, the parameter settings of the femtosecond laser are checked by the controller 460. After confirming that they are correct, the focal length of the Z-axis distance on the surface of the specimen 100 is adjusted by the hand box. Finally, the spot analyzer 450 is used to ensure that the spot diameter meets the requirements and the roundness of the spot reaches 90%. Then the femtosecond laser is started so that it can perform surface scanning and strengthening of the specimen 100 according to the predetermined parameter settings. The scanning path is set to a "Z" shape.
[0047] Step s300: Set the load and perform three-point fatigue tests on specimen 100 before and after strengthening. Specifically, after strengthening, ultrasonically clean specimen 100 with anhydrous ethanol for about five minutes to ensure the removal of residual stains on the surface of the strengthened material. Then, fix specimen 100 in the center on the three-point bending fixture, set the loading load according to GB / T 3075-2008 "Metallic Materials Fatigue Testing Axial Force Control Method" and GB / T 232-2024 "Metallic Materials Bending Test Method", then start the fatigue testing machine. After ensuring the fatigue testing machine starts normally, turn on the load protection module and observe the load fluctuation amplitude in real time.
[0048] Step s400: Calculate the bending fatigue limit of specimen 100 before and after strengthening, and perform a comparative analysis of the strengthening mechanism. Specifically, a three-point bending fatigue load is set according to the stepwise loading method, with a stress ratio of R=0.1 and a frequency of 100 Hz. The fatigue limit of specimen 100 is calculated based on the load and cycle number corresponding to the fracture level. Combining the results of the three-point bending fatigue experiment, the mechanism of ultrafast laser strengthening to improve the fatigue limit of materials is analyzed.
[0049] Example 1
[0050] The above-mentioned treatment process for improving the three-point bending fatigue limit of thin-walled titanium alloy specimens is implemented as follows:
[0051] Step s100: According to GB / T 38915-2020 standard, the main mechanical properties of TC4 titanium alloy sheet are as follows: tensile strength of 970 MPa, elastic modulus of 110 GPa, and Poisson's ratio of 0.342. The forged TC4 titanium alloy sheet was machined into standard flat specimens 100 (30 mm × 15 mm × 1 mm) using wire electrical discharge machining. Subsequently, according to GB 1327-2008 standard, the surface roughness of the reinforced surface of specimen 100 was controlled to Ra < 0.2 μm through mechanical grinding and precision polishing to obtain the ideal surface quality required for ultrafast laser strengthening. Finally, the treated specimen 100 was placed in an ultrasonic cleaning device and deep cleaned for 5 minutes using anhydrous ethanol as the cleaning medium to thoroughly remove surface contaminants and oxide layers, ensuring that the surface of specimen 100 reached an ultra-clean state, creating optimal conditions for subsequent ultrafast laser treatment.
[0052] Step s200: During the ultrafast laser shock peening process, the pre-treated specimen 100 is first precisely fixed on the worktable of the three-axis machining platform of the femtosecond laser, ensuring that the surface of the specimen 100 is perpendicular to the laser beam. The main technical parameters of the femtosecond laser are: center wavelength 1030 nm, pulse width 290-1000 fs, single pulse energy 0-200 μJ adjustable, repetition frequency 50 kHz, spot diameter 30 μm, and the spacing between adjacent spots is set to 15 μm, i.e., the overlap rate is 50%. After being collimated by the beam expander 410, the laser beam is introduced into the scanning galvanometer 430 system through a group of high reflectivity (>99.5%) mirrors 420, and finally focused on the surface of the specimen 100 by the F-theta field lens 440 (focal length 100 mm), forming a focused spot with a diameter of 30 μm. Before the strengthening process, the scanning path is set to a "Z" shape by the controller 460, and the scanning speed is 750 mm / s. The Z-axis position was precisely adjusted using a handheld control box to ensure the laser focus was on the surface of specimen 100. The spot diameter was confirmed to be (30±2) μm and the roundness to be >90% using a beam analyzer. After starting the femtosecond laser, a nitrogen protective atmosphere (flow rate 10 L / min) was used to prevent surface oxidation. The laser power stability (fluctuation <±2%) was monitored in real time throughout the entire process. After treatment, a uniform laser-induced periodic nanostructure was formed on the surface of specimen 100, significantly improving the surface integrity of the material.
[0053] It should be understood that in laser shock peening experiments, using a zigzag scanning path helps to uniformly cover the material surface, especially at the corners, avoiding uneven distribution of residual stress caused by uneven local treatment, thereby improving the surface strengthening effect and three-point bending fatigue performance.
[0054] Step s300: After laser strengthening treatment, specimen 100 is first ultrasonically cleaned in anhydrous ethanol for 5 minutes to thoroughly remove residual contaminants and oxide layers from the surface. After cleaning, specimen 100 is dried in a constant temperature and humidity environment (23±2℃, relative humidity 50±5%) for 24 hours. Subsequently, specimen 100 is precisely mounted on a three-point bending fatigue testing machine, ensuring that the centerline of specimen 100 is aligned with the axis of the upper support roller 200. Before installation, according to the formula:
[0055] L = (D + 3a) ± The distance L between the two loading rollers 300 below the three-point bending fixture is obtained, where D is the diameter of the loading roller 300 and a is the thickness of the specimen 100, both in mm. Setting L improves the stability of the testing process and the accuracy of the test results.
[0056] Meanwhile, in accordance with the requirements of GB / T 3075-2008 and GB / T 232-2024 standards, the test parameters were set as follows: a step-by-step loading method stress control mode was adopted, the stress ratio R=0.1, and the loading frequency was 100 Hz. Considering the limited load-bearing capacity of thin-walled components, the first-level bending stress was set to 30% of the material's yield strength, and the number of cycles for each level was set to 1×10. 6 If specimen 100 does not fail due to fatigue after the cycle under this load, it will automatically enter the next cycle according to the stress ratio R=0.1, and repeat the cycle until specimen 100 fails due to fatigue. Each test group shall contain at least 5 parallel specimens 100. Before starting the testing machine, a no-load operation check shall be performed first. After confirming that the equipment is running smoothly, the load protection function shall be activated (set the frequency fluctuation threshold ±10%).
[0057] Step s400: This experiment uses a step-by-step loading method for three-point bending fatigue testing. This method is mainly based on the linear cumulative damage theory and can obtain the high-cycle fatigue limit of specimen 100 with a smaller number of specimens 100 and less time cost. The specific experimental steps are as follows: For the unstrengthened matrix specimen 100, the first-level bending stress is set to 30% of the yield strength. In this embodiment, the research object is aerospace forged TC4 titanium alloy, whose yield strength is 870 MPa, and the first-level bending stress is set to 261 MPa. If the first 10 6 If specimen 100 has not fractured by the end of the cyclic loading, a second cyclic loading cycle will automatically continue with a stress increment of 10% (R=0.1). 6 The cycle is repeated until specimen 100 experiences fatigue fracture. The cycle number and loading level at fracture are recorded. The three-point bending fatigue limit value is then calculated using the following formula:
[0058] ,in, The stress value is the first-order stress value before fracture failure of the fatigue specimen 100. The number of cycles for specimen 100 at the fracture stress level. The maximum stress level was determined; experimental data were recorded, and the strengthening mechanism was analyzed based on the experimental data.
[0059] Please combine Figure 2 The diagram shows the cooperation between the specimen 100 and the support roller 200 and two loading rollers 300 of the three-point bending fatigue testing machine. The support roller 200 is located above the two loading rollers 300. The diameters of the support roller 200 and the loading rollers 300 are equal and set to 10 mm. Thus, the distance between the two loading rollers 300 is 13 mm.
[0060] Please combine Figure 3The diagram illustrates the femtosecond laser used in this embodiment. During ultrafast laser shock peening, the laser source 400 is continuously stimulated to emit radiation and amplify in the semiconductor laser, then stably outputs a laser beam. The beam passes through a beam expander 410, which increases the diameter of the laser beam and reduces the divergence angle to decrease the energy density, thus avoiding damage to subsequent optical components and maintaining the collimation of the beam during long-distance transmission. After being shaped by the beam expander 410, the beam is transmitted to a reflector 420. The high reflectivity coating of the reflector 420 changes the laser propagation direction, maintaining the beam characteristics while adapting to complex optical path designs. The laser beam is output from the reflector 420 to the scanning galvanometer 430. The reflector 420 (X / Y axis galvanometer) driven by a motor can swing at high speed, enabling rapid positioning of the laser in the processing plane. Finally, the laser beam reaches the field mirror 440, which eliminates the nonlinear error during galvanometer scanning and converts the angular displacement of the scanning galvanometer 430 into linear displacement on the plane, focusing the laser onto the surface of the specimen 100.
[0061] Please refer to Table 1, which shows the surface stress field distribution of specimen 100 before and after ultrafast laser strengthening with different parameters. To distinguish between tensile and compressive stress, the tensile stress values in the table are positive, and the compressive stress values are negative. After changing the ultrafast laser pulse width and energy, it was found that the surface stress state of specimen 100 changed from unstrengthened tensile stress to compressive stress. The stress amplitude reached its maximum at parameters of 290 fs / 200 μJ, 290 fs / 300 μJ, and 1000 fs / 300 μJ. Therefore, specimen 100 strengthened under these parameters was selected for three-point bending fatigue performance testing.
[0062] Table 1. Surface stress field distribution of specimens before and after ultrafast laser strengthening with different parameters.
[0063]
[0064] Please combine Figure 4 The figure shows a comparison of the three-point bending fatigue limit of specimen 100 before and after optimization based on stress data parameters. The average fatigue limit of the unstrengthened specimen 100 is 400.20 MPa (1,434,428 cycles), while after the optimal parameter treatment of 290 fs / 300 μJ, the average fatigue limit is increased to 459.95 MPa (3,141,416 cycles), an increase of 14.9%.
[0065] This embodiment also provides a processing system applied to the above-described process for improving the three-point bending fatigue limit of thin-walled titanium alloy specimens, comprising:
[0066] The pretreatment device, femtosecond laser, and fatigue testing machine are used to obtain specimen 100, the femtosecond laser is used to emit laser light to the surface of specimen 100 to strengthen specimen 100, and the fatigue testing machine is used to perform three-point fatigue tests on specimen 100 before and after strengthening.
[0067] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A treatment process for improving the three-point bending fatigue limit of thin-walled titanium alloy specimens, characterized in that, Includes the following steps: Step s100: Pre-treat TC4 titanium alloy sheet to obtain specimen (100). Step s200: The specimen (100) is subjected to ultrafast laser shock peening treatment. Step s300: Set the load and conduct three-point fatigue tests on the specimens (100) before and after strengthening. Step s400: Calculate the bending fatigue limit of the specimen (100) before and after strengthening, and conduct a comparative analysis of the strengthening mechanism; Step s100 includes cutting a TC4 titanium alloy sheet into a cut part according to a set size, grinding and polishing the cut part, then ultrasonically cleaning the cut part, and drying it to obtain the test piece (100). In step s200, a femtosecond laser is used to scan and strengthen the surface of the specimen (100) in a "Z"-shaped scanning path; In step s200, the operating parameters are set as follows: The pulse width of the femtosecond laser is set to 290-1000 fs, the pulse energy of the femtosecond laser is set to 50-200 μJ, the repetition frequency of the femtosecond laser is set to 45-55 kHz, the spot diameter of the femtosecond laser is set to 25-35 μm, and the overlap ratio of the femtosecond laser is set to 45-55%.
2. The treatment process for improving the three-point bending fatigue limit of thin-walled titanium alloy specimens according to claim 1, characterized in that: In step s300, the specimen (100) is ultrasonically cleaned with anhydrous ethanol, and the cleaned specimen (100) is positioned on the three-point bending fixture of the fatigue testing machine. After setting the loading load, the fatigue testing machine is started.
3. The treatment process for improving the three-point bending fatigue limit of thin-walled titanium alloy specimens according to claim 2, characterized in that: Before positioning the specimen (100) on the three-point bending fixture, the distance L between the two lower loading rollers (300) of the three-point bending fixture is adjusted using the following formula; L = (D + 3a) ± Where D is the diameter of the loading roller (300) and a is the thickness of the specimen (100), both in mm.
4. The treatment process for improving the three-point bending fatigue limit of thin-walled titanium alloy specimens according to claim 2, characterized in that: In step s400, a three-point bending fatigue test is conducted using a step-by-step loading method. The loading parameters are set as follows: stress ratio R = 0.1, loading frequency 100 Hz, maximum bending stress set to 30% of the material's yield strength, and the number of cycles per stage set to 1 × 10⁻⁶. 6 If the specimen (100) does not fail due to fatigue after the cycle under the load, it will automatically enter the next cycle according to the stress ratio R=0.1, and repeat until the specimen (100) fails due to fatigue. Each test group contains at least 5 parallel specimens (100).
5. The treatment process for improving the three-point bending fatigue limit of thin-walled titanium alloy specimens according to claim 4, characterized in that: In step s400, the bending fatigue limit of the specimen (100) before and after strengthening is obtained using the following formula. : ,in, The stress value is the first-order stress value before fracture failure of fatigue specimen (100). The number of cycles for specimen (100) at the fracture stress level. The maximum stress level was determined; experimental data were recorded, and the strengthening mechanism was analyzed based on the experimental data.
Citation Information
Patent Citations
Strengthening method for optimal combination of laser shock peening and shot peening
CN110438425A
Device and method for improving fatigue performance of conduit through femtosecond laser surface modification
CN114799530A
